Pricing warrant by using binomial model: comparison between historical and implied volatility / Khairu Azlan Abd Aziz … [et al.] - Abd Aziz, Khairu Azlan; Mohd Idris, Mohd Fazril Izhar; Wan Daud, Wan Suhana; Mazlan, Muhammad Nasruddeen (Universiti Teknologi MARA, Sabah, 2020)
A warrant is a security that allows the holder to buy and sell the underlying share at a fixed price until expiry date. Warrant price will always fluctuates since the underlying share also fluctuates. Hence, determining the warrant price is the main problem among the investors in Malaysia. This research is focusing on pricing the warrant for five companies that were listed in Bursa Malaysia. The companies were chosen randomly from UiTM DataStream. The selected companies were Boon Koon Sdn Bhd, Hovid Bhd, Kelington Bhd, ML Global Bhd and Tropicana Corporation Bhd. The data contained underlying share, interest rate, exercise price and actual warrant price. This research aims to define the price of warrant by using Binomial model. Historical volatility and implied volatility were used in this research whereby volatility is the movement of the underlying share price. This research aims at comparing the actual warrant price with the calculated warrant price. The data were computed manually by using Microsoft Excel and the comparison was made between the two type of volatilities to give the nearest value of calculated warrant price to the actual warrant price. The nearest value was assumed the best value for this research. The result was made by analyzing the line graphs and comparing between historical volatility and implied volatility with actual warrant price. Mean Square Error was used to support the results that were obtained from the line graphs. In the end, implied volatility yielded better results compared to historical volatility.